The role of health surveillance in the management of water quality in rural properties in seven municipalities of the Region of Paraná - Athaydes, Tiago Vinicius Silva; Crispim , Jefferson de Queiroz; Parolin , Mauro (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
Sanitation in rural areas in Brazil is still very precarious, with deficits greater than in urban areas. In this sense, the central objective of this research is to evaluate the role of the Municipal Surveillance in the management of water quality in rural properties in the Midwestern region of Paraná, covering the beginning of the monitoring of water quality, the relationship of the Consolidation Ordinance No. 5 of 2017 of the Ministry of Health regarding the choices of parameters on potability indices in relation to the parameters analyzed in the Surveillance, the presence of outbreaks due to diseases arising from the consumption of contaminated water, the demand by residents and the partners who contribute to the realization of these activities. The data were obtained through the application of a semi-structured questionnaire, through the 11th Health Regional Office of Campo Mourão. It was presented that the municipalities have acted in the monitoring of water quality in an uneven way at the beginning of the activities, following the parameters of the Ordinance. The municipalities had demands and demands from residents and counted on the 11th Health Regional Office as the main partner in the monitoring support. Only Iretama presented an outbreak due to the consumption of contaminated water.